Do Economists Play Well with Others? Experimental Evidence on the Relationship Between Economics Education and Pro-Social Behavior. (May 2014) - McCannon, Bryan C.
Does an economics education affect an individual's behavior? It is unclear whether differences in behavior are due to the education or whether those who choose to study economics are different. This issue is addressed using experimental evidence from the Trust Game where trusting and reciprocating behaviors can be measured. First, it is shown that economics students provide greater trusting investments and reciprocate more. Accounting for the selection effect, these effects are explained by those who choose to study economics and not directly from the education being provided. Thus, economists play well with others and these social preferences are not taught in the classroom.